Asset-Based Community Development in Realizing Sustainable Community in Untung Jawa Island Tourism Village - Rialny, Shaskia Shinta; Anugrahini, Triyanti (Universitas Muhammadiyah Ponorogo, 2022)
The Covid-19 pandemic become a significant threat on the sustainability of the Untung Jawa Island Tourism Village community. Government have taken measures that limit access to the tourist attraction during the pandemic, however this action caused the income of people who depend on the tourism sector was drop drastically. Asset-Based Community Development (ABCD) is a development approach from community and focuses on the potential and strengths of the community. The ABCD approach has been considered more capable of realizing a sustainable community, compared to the traditional need-based approach. This study aims to describe the community's strategy in managing assets in the Pulau Untung Jawa Tourism Village by using a qualitative approach that generate descriptive data. The results showed that the Untung Jawa Island Tourism Village Community has been able to maintain the survival of its community by maximizing the assets owned by the community independently and maintaining relationships between the community and all stakeholders who are connected to each other. Based on this results, they are currently able to survive the Covid-19 pandemic and always strive to create a sustainable community in the future.